In Good Company Sixty Years with the Royal Ballet. Review - Sansom, Bruce (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of Leslie Edwards's In Good Company. PALABRAS CLAVE: Leslie Edwards, Royal Ballet.
In Good Company: Sixty Years with the Royal Ballet. Leslie Edwards, Dance Books.